University and ICT: a case study of an educational experience in Salta (Argentina) in the context of a pandemic - Chachagua, Maria Rosa (2021)
In Argentina, since March 2020, face-to-face classes have been suspended throughout the country, as a result of the COVID-19 pandemic. Therefore, the education system had to adapt to the distance education modality, and the universities were not the exception. In that transition, different problems emerged related to the didactics (organization, planning) but above all, access to ICT (New information and communication technology) and transmedia literacy. The ICT mediated education format deepened existing inequalities, that is, the material, social, educational, cultural, and psychological of family conditions. This article proposes a case study of the annual cathedra at the National University of Salta. It systematized the extended classroom experience in a previous pandemic period, where some tools like Classroom, a blog, and a Facebook page were used and later the use of virtual classroom on the Moodle platform. The work obtained data from two surveys carried out on students at the cathedra and the observation of the uses of the mentioned platform. Finally, as part of the conclusion of the work, it is proposed that the extended classroom is a more viable option for the return to face-to-face classes in the immediate context (post-pandemic).